Performance assessment of waste fibre-reinforced mortar - Pereira, Cristiana Gonilho (2013)
In this paper an experimental work is presented which main objective is the evaluation of the influence of different percentages of waste fibrous materials usage on the performance of fiberreinforced mortars. Moreover, the influence of binder type is evaluated. Therefore mortars were produced with two different binders – cement and powder hydrated lime. Mortars performance evaluation was carried out through flow table and plunger penetration consistency, dynamic modulus of elasticity, flexural and compressive strength, capillary absorption, drying index and adherence tests. The benefits revealed in some characteristics of both mortars by the use of waste fibers are discussed.